Landscape architectural graphic standards - Hopper, Leonard J. (Hoboken, N.J. : John Wiley and Sons, 2007)
Landscape Architectural Graphic Standards is an entirely new, definitive reference work for everyone involved with landscape architecture, design, and construction. Based on the 70-year success of Architectural Graphic Standards, this new book is destined to become the ?bible? for the landscape field
Preface -- Acknowledgments -- part 1. Practice of landscape architecture -- General -- Overview of profession -- Construction documentation -- Overview of construction documentation -- Project manual -- Construction drawing layout -- Symbols -- Landscape planning -- Environmental and Legal -- Environmental review -- Legal : permits and regulations -- Project administration -- Project management -- Business administration : records, legal, liability -- Cost estimating -- Bidding -- Construction observation -- Postoccupancy evaluation -- part 2. Standards and guidelines -- Human factors -- Human nature and spatial relationships -- Community participation -- Environmental factors -- Modifying solar radiation -- Modifying wind -- Regional climate -- Modifying microclimates -- Modifying air quality -- Brownfields evaluation -- Environmental hazards -- Wetlands evaluation -- Resource inventory and conservation -- Sustainable site design -- Cultural factors -- Historic landscape -- Security considerations -- Crime prevention through environmental design -- Site security planning and landscape design criteria -- Site planning -- Environmental site analysis -- The town planning process -- Rural village design -- Elements of urbanism -- Plan types -- Block types -- Open space types -- Building types -- Spatial definition -- Frontage types -- Landscape types -- Traditional neighborhood design -- Site planning for fire protection -- Residential site planning -- Residential density -- Single-family detached housing -- Single-family attached housing -- Context-sensitive solutions -- Transit-oriented development -- Circulation -- Vehicular circulation -- Parking standards -- Parking lot design guidelines -- Parking space dimensions -- Parking lot design -- Accessible parking -- Bicycle circulation -- Recreational trails and shared-use paths -- Accessibility -- Access to the outdoor setting -- part 3. Process, implementation and application -- Construction operations and earthwork -- Site construction overview -- Soil mechanics -- Embankment stabilization -- Site grading and earthwork -- Cut and fill calculations -- Water supply and management -- Subsurface drainage systems -- Surface drainage systems -- Runoff control systems -- Wetland preservation -- Wastewater management : graywater harvest and treatment -- Constructed treatment wetlands -- Stormwater management -- Site design for stormwater management -- Stormwater hydrology -- Stormwater conveyance -- Stormwater quantity control -- Stormwater quality control -- Rainwater harvesting -- Stream restoration -- Irrigation and water features -- Irrigation -- Water features, fountains, and pools -- Fountains and decorative pools -- Garden structures -- Pavement and structures in the landscape -- Pavement in the landscape -- Unit pavers -- Concrete pavement -- Asphaltic concrete pavement -- Porous pavements -- Stairs, ramps, and curbs -- Freestanding and retaining walls -- Fences and screens -- Gazebos and freestanding wood structures -- Overhead structures -- Wood decks -- Wood decking -- Site amenities -- Lighting -- Planting -- Soils : urban or disturbed -- Public planting design principles -- Residential landscape design principles -- Environmental effects of trees -- Site considerations, plant installation requirements, and details -- Tree planting in urban areas -- Planting : special considerations -- Recommended ornamental and shade trees for use in landscape design in the continental United States -- Native species : Upper Midwest -- Native plants -- Xeriscape design -- Construction damage to existing trees on-site : avoidance, protection, and preservation -- Plant maintenance -- Interior plants -- Turf -- Living green roofs and landscapes over structure -- Special construction -- Plaza membrane waterproofing over occupied space -- Therapeutic gardens -- Wildlife habitat -- Campuses -- Hazard control -- Soil erosion and sediment control -- Restoration and remediation -- Ecological community restoration -- Brownfields remediation and development -- Sound control and reduction -- Parks and recreation -- Large city parks -- Small urban parks -- Waterfronts -- Outdoor play areas -- Golf course design : planning and details -- Waste management -- Solid waste collection and recycling spaces -- part 4. Materials -- Soils -- Soils : agronomic -- Asphalt -- Asphalt -- Concrete -- Concrete -- Concrete reinforcement : reinforcing bars and wire -- Environmental and health considerations of concrete -- Masonry -- Brick masonry -- Concrete masonry units -- Metals -- Metal -- Wood -- Wood and related products -- Recreational surfaces -- Recreational surfaces -- Nursery stock -- Nursery stock standards and practices, shipping and handling, guarantees -- Other materials -- Greenhouses -- Geotextiles -- Paints and coatings -- Evaluating the environmental and human health impacts of materials -- Life-cycle phases of a material or product -- Inputs and outputs associated with building materials/products -- Green building materials defined -- Evaluation tools -- Index.
Includes index.
Includes bibliographical references and index.
Keywords: Landscape architecture; Landscape design